Electrocatalytic nitrate reduction to ammonia via amorphous cobalt boride. Issue 62 (14th July 2022) - Shi, Yongbin; Xu, Suxian; Li, Fei
Abstract : Amorphous CoB x nanoparticles supported on carbon paper were synthesized by a simple wet chemical reduction method, and exhibited remarkable performance toward electrochemical nitrate reduction. Abstract : Electrocatalytic nitrate reduction reaction (NitRR) is an energy-saving and environmentally benign approach to synthesizing ammonia under ambient conditions. However, the development of noble metal-free catalysts with high activity and selectivity is still a significant challenge. In this study, uniformly dispersed amorphous CoB x nanoparticles supported on carbon paper were synthesized via a simple wet chemical reduction method. As an efficient nitrate reduction electrocatalyst, CoB x exhibited a maximum faradaic efficiency of 94.00 ± 1.67% and a yield rate of up to 0.787 ± 0.028 mmol h −1 cm −2 for ammonia production. The enhanced NitRR performance could be attributed to a partial electron transfer from B to Co, which is necessary for optimizing the adsorption energies of the reaction intermediates and facilitating electron transport. Thus, selective and cost-effective electroreduction of nitrates to ammonia can be achieved using CoB x nanoparticles.